Exploring how multi-year cover crop use alters above and belowground weed communities in limited tillage corn–soybean systems - Oys, Elizabeth; Krupek, Fernanda Souza; Proctor, Christopher; Koehler-Cole, Katja; Basche, Andrea (Frontiers in Agronomy, 2025)
Over the last several decades, the intensive production of corn (Zea mays L.) and soybeans (Glycine max L.) in the United States has included the widespread use of herbicide-tolerant crops, contributing to soil management with reduced tillage. The continuous use of herbicides with the same modes of action has led to the accelerated development of herbicide resistance in weed populations, particularly from the Amaranthaceae family. Integrated weed management tools, such as the use of cover crops, have increasingly been recognized as cultural approaches with the potential to reduce herbicide-driven selection pressure. We utilized six multi-year (4–7 years) cover crop research trials in corn-based crop rotations to measure germinable weed seedbanks, aboveground weed density, and biomass. This included four on-farm and two university research experiments across eastern and central Nebraska, with histories of no tillage or reduced tillage. Three sites showed increases in Amaranthaceae family (pigweed) seedbank densities under cover crops (137%–355%) compared to the no cover crop check, but no differences in total weed seed bank densities were found. Cover crops reduced aboveground total weed density and biomass at the two sites; however, increases from the pigweed seedbank were not observed at any site. Multivariate analyses revealed that the species composition of the seedbanks under cover crops was distinct from that of the check at the two sites, suggesting that cover crops may influence weed seedbank composition over time. This work underscores the value of exploring integrated weed management, as well as monitoring weed populations in the soil seedbank and aboveground emerged species, particularly in cropping systems with reduced soil disturbance. We encourage more research on the multi-year use of integrated weed management approaches, such as cover crops, to better understand the complexity of how such approaches shift weed communities, especially with respect to herbicide-resistant weeds.